Green-go: A green innovation competitiveness index - Bernardina Algieri; Antonio Aquino; Marianna Succurro (Sustainable Futures, 2025)
This study proposes a Green Innovation Competitiveness Index based on green patents, presented in both general and adjusted-symmetric versions. The suggested index is suitable for computing the green innovation competitive advantage or disadvantage of countries and, hence, analysing the green specialisation and geographical patterns of green innovations around the world. The symmetric innovation competitiveness index has been combined with international trade data and used as an additional explanatory variable of export determinants for a group of countries (China, France, Germany, Japan, Italy, Spain, the UK and the USA), thereby capturing the non-price green competitiveness of these countries. The empirical evidence indicates that both non-price green and non-green competitiveness have a positive impact on export volumes. The suggested index can be useful for future developments of cross-country empirical analysis and the design of effective policy measures.